Overcoming policy, finance, and technology supply constraints to unleash small-scale irrigation in Nigeria - Balana, Bedru; Yakasai, Musa T.; Musa, Nuruddeen M.; Iraoya, Augustine Okhale; Ringler, Claudia (International Food Policy Research Institute, 2025)
Nigeria is suffering from high levels of food insecurity, with 25 million people at risk of hunger and 34% of children under 5 stunted (low height for age) due to lack of access to nutritious food among other reasons. In 2023, the government declared a state of emergency for food security.